IMPLEMENTASI WAJIB BELAJAR 12 TAHUN PADA ORANG RIMBA DI BUKIT 12 KECAMATAN AIR HITAM KABUPATEN SAROLANGUN PROVINSI JAMBI - Tyo Sandiago; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: This research was motivated by the implementation of the 12 Year Government Program in Orang Rimba, Air Hitam Subdistrict, Sarolangun Regency. The formulation of the problem in this study is 1) What caused Orang Rimba to be afraid of the gods for carrying out education 2) How is the implementation of the 12 year compulsory education for the Orang Rimba Kecamatan Air Hitam, Kabupaten Sarolangon, Provinsi Jambi. The purpose of this study was to find out whether the 12 year compulsory education program was implemented in the Orang Rimba Kecamatan Air Hitam, Kabupaten Sarolangun, Provinsi Jambi. The method of this research is qualitative descriptive. The informants in this study were Tumenggung, SAD School Teachers who were determined using purposive sampling technique and combined with snowbaling sampling techniques. Data was collected through interviews, observation, and documentation with triangulation techniques. From the results of the study it can be concluded that there are those in the Children Tribe who have implemented 12 year compulsory education, but some have not. Those who have implemented 12 year compulsory education have the enthusiasm to learn and their parents approve their children to carry out education, while for children in Inner Tribe who have not implemented 12 year compulsory education because most of them are not allowed by their parents to carry out education because they often invited by their Parents to Build (Wander / Wander). So that their learning process is hampered because they are often invited to Build by their Parents.Key Words: Must Learn 12 Years, Suku Anak Dalam, Orang Rimba